2008
DOI: 10.1007/s11224-008-9364-1
|View full text |Cite
|
Sign up to set email alerts
|

Chlorodiphenyltin(IV) and triphenyltin(IV) complexes of N-alkylated 2-amino-1-cyclopentene-1-carbodithioic acids: synthesis, spectroscopic characterization and X-ray studies

Abstract: Four new complexes, [Ph 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…IR bands were assigned by comparison with the spectra of Bz-HACDA and Pr-HACDA and with previously reported data (Tarassoli et al, 2006;Hanif et al, 2008). A band in the 3340-3350 cm -1 region is assigned to the ν(NH) stretching mode (Chauhan et al, 1984), which shows no significant shift from that of the free ligand, indicating that this functional group is not involved in the coordination to tin.…”
Section: Ir Spectra Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…IR bands were assigned by comparison with the spectra of Bz-HACDA and Pr-HACDA and with previously reported data (Tarassoli et al, 2006;Hanif et al, 2008). A band in the 3340-3350 cm -1 region is assigned to the ν(NH) stretching mode (Chauhan et al, 1984), which shows no significant shift from that of the free ligand, indicating that this functional group is not involved in the coordination to tin.…”
Section: Ir Spectra Analysismentioning
confidence: 80%
“…In the last decade, various investigations have been reported on the synthesis of complexes of diorganotin(IV) (Tarassoli et al, 2006;Hanif et al, 2008) with ACDA type ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In the following paper, Hanif et al [262] reported the synthesis and characterization of two triphenyltin(IV) and two chlorodiphenyltin(IV) complexes of N-substituted, N-alkylated 2-amino-1-cyclopentene-1-carbodithoic acid (ACDA) complexes: [Ph 3 Sn(isopropylACDA)], [Ph 2 SnCl (isopropylACDA)], [Ph 3 Sn(secbutylACDA)] and [Ph 2 SnCl (secbutylACDA)]. The authors used FTIR, multinuclear NMR and mass spectrometry to characterize all four complexes.…”
Section: Issuementioning
confidence: 99%
“…In methyl derivatives (1), (4) and (7) small satellites are clearly visible along with the chemical shift value of the methyl moiety, providing 2 J[ 119 Sn, 1 H] coupling values of 57, 75 and 79 Hz, respectively. These values correspond to C-Sn-C bond angle of 110°, 125°and 130°thus suggested four (1) and penta-coordinated (4 and 7) Sn [4,[18][19][20]. Chemical shifts of n-butyl and aromatic protons are difficult to assign because of their peaks multiplicity and consequently overlapping of signals.…”
Section: Nmr Spectroscopymentioning
confidence: 99%